APLIKASI HORMON BAP, NAA, AIR KELAPA TERHADAP MULTIPLIKASI PISANG CAVENDISH (Musa acuminata L.) SECARA IN VITRO - Asri Pirade Paserang; Riska Riska (Biocelebes, 2022)
This study aims to determine the effect of proper concentration of coconut water on the shoot multiplication of cavendish banana (M. acuminata L.) with the addition of the NAA and BAP hormones. This study used a Completely Randomized Design (CRD) with 8 treatments. Each treatment repeated 3 times. Therefore, there were 24 experimental units. Each unit using 1 explant so there were 24 explants. The treatments consisted of: A1 (0% coconut water + 0.2 ppm NAA), A2 (15% coconut water + 0.2 ppm NAA), A3 (20% coconut water + 0.2 ppm NAA), A4 (coconut water 25% + NAA 0.2 ppm), A5 (0% coconut water + BAP 2 ppm), A6 (15% coconut water + BAP 2 ppm), A7 (20% coconut water + 2 ppm BAP) and A8 (coconut water 25% + BAP 2 ppm). The parameters observed were days to the emergence of shoots, number of shoots and percentage of the number of shoots. The results showed that the addition of the 2 ppm BAP hormone which is in treatments A7 showed the fastest emergence of shoots with an average of 8 DAP and the average number of shoots that appeared was 2,67 and the percentage of the number of shoots was 88,89%.